2020
DOI: 10.32615/bp.2019.136
|View full text |Cite
|
Sign up to set email alerts
|

Silicon alleviates salt and drought stress of Glycyrrhiza uralensis plants by improving photosynthesis and water status

Abstract: Silicon has been widely reported to have a beneficial effect on improving plant tolerance to biotic and abiotic stresses. However, the mechanisms of Si in mediating responses to simultaneous salt and drought stresses are still poorly understood. Glycyrrhiza uralensis Fisch. is classified as a non-Si accumulator and suffered from salt and drought stresses. In this study, we investigated the long-term application of Si on Si content in G. uralensis roots, stems and leaves, leaf anatomy, ultrastructure, chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 64 publications
3
22
2
Order By: Relevance
“…The VIS plants showed a significant reduction in Chlb, total Chl and relative Chl content compared with control plants. This is consistent with the report that the Chlb content decreased in virusinfected apple leaves (Bertamini et al, 2002) and suggests that Chlb was more sensitive than Chla to similar stress conditions, as reported by Palanisamy et al (2009) and Zhang et al (2020). Previous research has suggested that a decrease in the Chl content of infected leaves might reduce P N (Funayama et al, 1997;Sayed, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…The VIS plants showed a significant reduction in Chlb, total Chl and relative Chl content compared with control plants. This is consistent with the report that the Chlb content decreased in virusinfected apple leaves (Bertamini et al, 2002) and suggests that Chlb was more sensitive than Chla to similar stress conditions, as reported by Palanisamy et al (2009) and Zhang et al (2020). Previous research has suggested that a decrease in the Chl content of infected leaves might reduce P N (Funayama et al, 1997;Sayed, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, previous research indicated how water de cit caused variations in the decrease of fresh and dry biomass in T. aestivum L. (Pour-Aboughadareh et al, 2019) and Tetraena mandavillei L. (Alam et al, 2021). The interaction between Si and mycorrhiza did not cause a substantial difference in licorice biomass production but, contrary to the present study, several studies have shown that Si and mycorrhiza can increase plant biomass in Glycyrrhiza uralensis (Zhang et al, 2020), Arachis hypogaea L. (Patel et al, 2021), and Nicotiana tabacum L. (Begum et al, 2021). This increase in plant biomass supposedly occurs by a higher rate of carbon assimilation and photosynthesis.…”
Section: Discussioncontrasting
confidence: 58%
“…We showed that silicon application alleviated the negative effects of salt stress to a certain extent with the extent of the mitigating effect depending on the liquorice species. Although some investigations on the effect of silicon on the growth of liquorice under salt stress have been reported [50][51][52] , this is the rst report demonstrating that foliar spray with silicon enhances the salt tolerance of G. uralensis and G. in ata.…”
Section: Discussionmentioning
confidence: 84%
“…These observations suggest that silicon promotes the biosynthesis of photosynthetic pigments under salt stress. This may be attributed to the notion that silicon alleviates the damage to chloroplast under salt stress 51 , enhances RuBisCo protein expression, and promotes the synthesis of chlorophyll and carotenoids 48 . Similarly, foliar spraying with silicon alleviated the negative effects of salt stress on gas exchange parameters in the two liquorice species (Fig.…”
Section: Discussionmentioning
confidence: 99%